Just One Day: Just One Day Series #1 - Forman, Gayle (New York, N.Y. : Dutton Books, 2013)
"Sparks fly when American good girl Allyson encounters laid-back Dutch actor Willem, so she follows him on a whirlwind trip to Paris, upending her life in just one day and prompting a year of self-discovery and the search for true love."--
Keywords: Voyages and travels -- Fiction; Self-actualization (Psychology) -- Fiction; Love -- Fiction; Actors and actresses -- Fiction; Europe -- Fiction